Pembekalan Akuntansi Piutang Dagang Bagi Siswa SMA Kristen Yusuf - Yanti, Yanti; Dhea, Dhea (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2025)
Pengabdian kepada Masyarakat (PKM) was held on Friday, May 9, 2025, at 10:00 a.m., onsite at SMA Kristen Yusuf, with the goal of improving students’ understanding of accounts receivable as a key topic in financial accounting. The training involved 21 senior high school science students and was conducted using three interactive methods: (1) module-based theoretical instruction, (2) group discussion with contextual practice questions, and (3) a quiz game session as feedback and reinforcement. The students actively participated in all sessions and showed a clear increase in comprehension, especially through collaborative discussion and gamified learning. This PKM activity effectively bridged accounting theory with practical application in a high school setting, demonstrating that interactive, context-driven financial literacy programs can significantly enhance student engagement and understanding.